Does the use of surgical face masks reduce postoperative infections in traumatic wounds sutured outside hospital? A randomized study at a Norwegian casualty center - Kristoffer Holen Sælen; Synne Hatlemark; Christina Brudvik; Torbjørn Hiis Bergh; Soosaipillai V. Bernardshaw; Knut Steen (Taylor & Francis Group, 2024)
AbstractObjective To investigate if wearing surgical face mask by doctors and nurses during suturing of traumatic wounds has any impact on postoperative infection rate.Design Randomized controlled study with masked or unmasked health personnel groups.Setting A Norwegian Minor Injury Department.Subjects Adult patients with traumatic wounds sutured at the clinic between 7 October 2019 and 28 May 2020.Main outcome measures Postoperative infections of sutured wounds.Results One hundred and sixty-five patients with 176 wounds were included in the study. Nine out of 88 wounds (10.2%) in the masked group and 11 out of 88 wounds in the unmasked group (12.5%) had a wound infection.Conclusions Despite a higher percentage of postoperative infections in the unmasked than in the masked group (12.5% versus 10.2%), the difference was not statistically significant (p = .6). This might imply that the use of facemasks during suture of traumatic wounds in an outpatient setting does not significantly reduce the number of infections. However, due to the covid pandemic, the study had to be prematurely stopped before the planned number of participants had been recruited (n = 594). This increases the risk of type II error.